The Readers’ Attitude Towards the Realization of Bahasa Indonesia – English Code Switching in Looks Magazine - Meifahmi Intan (Passage, 2013)
This study investigates types and functions of code switching in “Mailbox” and “Readerstyle” columns of LOOKS magazine and the readers’ attitude towards the code switching. Document analysis was occupied to classify types and functions of code switching in the magazine whereas questionnaires were distributed to find out the readers’ attitude towards code switching in the magazine. Ten students from English Education Department are purposively chosen as the respondents. This study is framed within the theories of Poplack (1980), Koziol (2000) and Garret (2010). The findings reveal intra-sentential switching as the type which dominates the discourse in the magazine (62.50 %). Meanwhile, emphasis function is the most frequent function occurs in the magazine (45.39 %). Regarding the readers’ attitude, the majority of the respondents seem to have a positive attitude towards code switching in the magazine. Keywords: Bilingual, LOOKS magazine, code switching types, code switching functions, readers’ attitude